Learning from Errors in Numbers and Number Operations in Early School Mathematics - ARORA, ANCHAL (THE PRIMARY TEACHER, 2016)
Errors are an inevitable part of the learning process. This article begins with the need to re-conceptualise errors in the learning of mathematics from obstacles or hindrance to insights to learners’ thinking process, and opportunities for learning. The latter section of the article focuses on error analysis with reference to the concept of numbers in early school mathematics. It discusses what error analysis means and how it can play an important role in integrating assessment with learning, as well as, help shift focus from right or wrong answers to a broader meaning of learning in mathematics